Water use efficiency and economic return of fresh vegetable in organic cultivation - Daniel F. de Carvalho; Marinaldo F. Pinto; José A. Monte; Gabriel A. B. de Mello; Camila P. de Sousa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The optimization in the use of irrigation is a necessity due to water scarcity and the increasing demand for food. The objective of this study was to evaluate the effect of different irrigation depths on the economic efficiency of lettuce, eggplant, beet and carrot, cultivated in an organic production system. The evaluations were performed based on production functions obtained in field experiments conducted from 2006 to 2011, and survey of prices of products and inputs, determining the irrigation depths corresponding to the maximum gross profit and the maximum water use efficiency. Additionally, the relative yield reduction was evaluated for different percent increments in the economically optimal irrigation depth. It was observed that the crops have differences between the irrigation depths of maximum economic efficiency and maximum water use efficiency, ranging from 22.2 mm (lettuce) to 149.7 mm (eggplant). The application of water above the irrigation depth of maximum economic efficiency led to yield and profit reductions, whose magnitude depends on the response of the crop.